Three-Dimensional Biomechanical Analysis of Movement Patterns Associated with Anterior Cruciate Ligament Injuries in Football Players - Muthanna Harith Ekrayyem; Maysaa Khalid Ahmed (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Anterior cruciate ligament (ACL) injuries are common and serious musculoskeletal injuries in football, due to their negative impact on players’ health, the continuity of their sporting careers, and individual and team performance levels. Three-dimensional biomechanical analysis is an objective and accurate tool for identifying movement patterns associated with an increased risk of injury, particularly those that are difficult to observe or assess effectively using traditional two-dimensional analysis methods. The study aimed to determine the three-dimensional kinematic and kinetic characteristics of the lower limbs during the performance of high-risk movement tasks similar to those required in football among players from three clubs in the Iraqi Premier League, as well as to compare biomechanical risk indicators between the clubs and to reveal the relationship between specific movement patterns and the composite risk of anterior cruciate ligament injury. A descriptive, cross-sectional study design was employed. The study sample comprised sixty male football players, with twenty players from each of the Al-Samarra, Al-Alam and Al-Dour clubs. Data were collected using the VICON Nexus 3D motion capture system, comprising 12 cameras at 200 Hz, two Kistler force plates at 1000 Hz, and the Noraxon Ultium system for measuring electromyography (EMG) at 2000 Hz. The players performed three standardised movement tasks: a 45-degree cut on one leg, a two-foot landing after a jump, and a 180-degree turn. The main variables included the maximum internal knee varus angle, peak ground reaction force, lower limb joint flexion angles at the moment of first contact, and the joint muscle contraction index. The results showed statistically significant differences between the clubs in knee varus angle, with an F-value of F(2,57) = 8.34, a significance level of p = 001., and an effect size of η² = .226, as well as in peak ground reaction force (F(2,57) = 6.21, p = 00.3, η² = 179.) and in knee flexion angle (F(2,57) = 7.85, p = 00.1, η² = 216.). The knee varus angle also showed the strongest correlation with the composite risk score for anterior cruciate ligament injury, with a correlation coefficient of r = 82. at a significance level of p < .001. Group analysis revealed two distinct risk profiles: the first was a high-risk biomechanical profile, characterised by a marked increase in knee varus and a reduced knee flexion angle; the second was a low-risk profile, characterised by a better degree of protective co-contraction. IIraqi footballers in the clubs included in the study exhibited biomechanical patterns associated with an increased risk of anterior cruciate ligament injury whilst performing football-specific motor tasks. Differences between clubs suggest that risk indicators may be influenced by multiple factors, including the nature of training programmes, pitch surface characteristics, and the level of strength training and neuromuscular control. The study’s findings underscore the importance of implementing targeted preventive programmes to reduce ACL injuries in Iraqi football clubs.